2015
DOI: 10.1007/s00330-015-3993-8
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of complex aortic aneurysms: prevalence of acute kidney injury and effect on long-term renal function

Abstract: ObjectivesTo analyse predictors for short- and long-term renal function changes after fenestrated and branched endovascular aortic repair (EVAR).MethodsA total of 157 patients underwent fenestrated and branched EVAR. Procedural intra-arterial iodinated contrast volume was documented. Serum creatinine and estimated glomerular filtration rate (eGFR) at baseline, during 48 h following EVAR, at discharge and latest moment of follow-up were recorded. Development of post-EVAR acute kidney injury (AKI; according to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…The incidence of AKI was 18% in our study, which is consistent with that of previous studies (19%-29%) (7,18). Incidence may vary across studies for various reasons, one of them being the difference in classification of AKI.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of AKI was 18% in our study, which is consistent with that of previous studies (19%-29%) (7,18). Incidence may vary across studies for various reasons, one of them being the difference in classification of AKI.…”
Section: Discussionsupporting
confidence: 92%
“…28 They showed that 43 of 156 (28%) patients undergoing branch or fenestrated repairs developed AKI with a univariate statistically significant difference in contrast material volumes between the two groups. The event rate in their cohort is too low to support the proposed nine covariate multivariable logistic regression, which is further confounded by more than double the number of accessory renal arteries covered in the AKI group in comparison to the no AKI group.…”
Section: Discussionmentioning
confidence: 99%
“…44 Following the publication of our meta-analysis, Sailer et al 46 reported an AKI incidence of 28% using the AKIN criteria in 157 patients undergoing fEVAR or bEVAR and Ducasse et al 47 reported an incidence of 32% in a similar fEVAR population. Following the above, it is clear that the incidence of AKI after EVAR has previously been underestimated and true incidence is close to 15-20% in up to date series using acceptable reporting criteria.…”
Section: Introductionmentioning
confidence: 91%